Rapid and Sensitive Diagnosis of Drug-Resistant FLT3-F691L Mutation by CRISPR Detection - Liu, Yin; Chen, Yanling; Huang, Shisheng; Ma, Xiaodong; Huang, Xingxu; Wang, Xinjie; Zhou, Fuling (Frontiers in Molecular Biosciences, 2021)
Sensitive and efficient detection of drug-resistant mutations is essential in cancer precision medicine. In treating acute myeloid leukemia (AML), FLT3 gene F691L mutation shows universal resistance to all currently available FLT3 inhibitors. However, there is no particular detection method for FLT3-F691L. Commonly-used first-generation sequencing (FGS) approaches have low sensitivity, and next-generation sequencing (NGS) is time-consuming. Herein, we developed an accurate and sensitive FLT3-F691L diagnostic method by CRISPR detection. Briefly, the FLT3-691 region is amplified by recombinase polymerase amplification (RPA) and detected by L691-crRNA induced Cas12a reaction, and finally the result can be directly observed under a blue lamp or analyzed by a fluorescence reader. Confirmed by the tests on diluted plasmids and 120 AML patient samples, this method can achieve a sensitivity of 0.1% and complete the whole diagnosis process within 40 minutes. Potentially, this method will play an important role in point-of-care applications and guidance of AML treatment.